Evaluation of the efficiency of an integrated biofilm and phytoremediation system with Nasturtium officinale for the treatment of municipal wastewater in Huancavelica - Álvarez Ticllasuca, Adiel (2021)
In this research removal efficiency was evaluated of organic pollutants of a biofilm and phytoremediation integrated system for municipal wastewater treatment in Huancavelica. A pilot plant consisting of a settler was installed that also retained oils and fats, a biological filter using as support material the calcareous stuff and a phytoremediation process with Nasturtium officinale (watercress) The hydraulic retention time was 5.5 hours and the flowrate of 0.011 L s -1, the evaluation was made of the proper functioning of processes by monitoring control parameters. The pollutant removal efficiency was determined by Student's "t" test (p <0.05). An average pH value of 7.57 and a temperature of 12.07 ° C were obtained, subsequently the measurement of BOD5 was initiated, obtaining maximum effluent values of 131 ppm and minimum values of 45 ppm and a removal efficiency of 44.8% was obtained, for COD. In total coliforms, fecal coliforms and Escherichia coli the removal was 66.67%, 94.59%, 81.22% and 72.12% respectively, oil and fat analysis was also performed and total suspended solids, however high removal efficiency was not obtained. It is concluded that the parameters of BOD5 and COD comply with the MPL for the effluents of municipal domestic wastewater treatment plants, while the rest of the parameters analyzed do not comply with the regulations. however high removal efficiency was not obtained. It is concluded that the parameters of BOD5 and COD comply with the MPL for the effluents of municipal domestic wastewater treatment plants, while the rest of the parameters analyzed do not comply with the regulations. however high removal efficiency was not obtained. It is concluded that the parameters of BOD5 and COD comply with the MPL for the effluents of municipal domestic wastewater treatment plants, while the rest of the parameters analyzed do not comply with the regulations.